Identifikasi Kerang Kapah Di Pantai Timur Pulau Tarakan - Abdul Jabarsyah; Takeshi Arizono (Journal Omni-Akuatika, 2016)
We identified the species of “kerang kapah” (hard clam) using the Gel Electrophoresis SDS Page, inorder to clarify the species of kerang kapah those found living along the East Coast of TarakanIsland. The study was conducted from July to December 2014. The kerang kapah were collectedfrom the several parts of East Coast Tarakan Island. Eight group samples of kerang kapah were used for Gel Electrophoresis SDS Page and scanned using the IMAGE software. Generally, thekerang kapah those found at the shouth part of East Coast of Tarakan Island have very similarmorphologies and shell colors, making species identification difficult.  Four species of kerang kapahwere identified. Three species belong to Veneridae and one species belong to Corbiludae. Thespecies of Veneridae were Meretrix meretrix, Meretrix lyrata, and Meretrix sp. The species karangkapah belong to Corbiludae is Polymesoda erusa.Keywords: kerang kapah, meretrix, polymesoda, gel electrophoresis.